Art, critical pedagogy and capitalism - Stewart, Paul Alexander, 1990- (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"This book offers a re-examination of art production in terms that understand the process of learning as the production of art itself. Drawing on the thought of Ranciere, Freire, Gramsci and Mouffe, it provides an account of the politics of art production and a theoretical understanding of hegemonic power, while developing a view of method in critical pedagogy founded on the process of 'making adversaries'. Through a re-evaluation of the relationships between process, arts production and pedagogy within accelerated developments of neoliberalism, the author uncovers ways of forming a more co-operative and less conflictual approach to democratic politics. An investigation of ways in which art practice can be used to engage with critical pedagogy in relation to a commodity driven neoliberal agenda, Art, Critical Pedagogy and Capitalism constitutes a radical rethinking of art making, and an attempt to address the paradox between the proliferation of the commodity of learning and the perceived crisis of arts education. As such, it will appeal to scholars of education, pedagogy and the arts with interests in social and critical theory"--
Introduction -- Agonising over and under Hegemony -- Commitment -- Tools and Social Action -- Action and Reflection -- Boycott.
Outgrowth of the author's thesis (Ph.D.)--Teesside University, 2019, under the title: Art, hegemony and the alternative art school : critical pedagogy as a methodology in art practice.
OCLC-licensed vendor bibliographic record.
Keywords: Art -- Economic aspects; Alternative schools; Critical pedagogy; SOCIAL SCIENCE / Sociology / General